Epidemiology of environmental enteric dysfunction, malnutrition and intestinal microbiota amongst children in Kilifi, Kenya - Crane, R (2019)
Environmental Enteric Dysfunction (EED) is a chronic intestinal inflammatory disorder that is highly prevalent amongst children in tropical low-income settings and associated with stunting (low height-for-age). I undertook two studies in coastal Kenya that aimed to explore the aetiology of EED. Firstly, in a cross-sectional survey across 12 villages, 509 under-fives from 229 randomly selected homesteads underwent anthropometry and provided a stool sample. Participant sociodemographic and health characteristics were determined by questionnaire. 419 stool samples underwent enzyme-linked immunosorbent assay (ELISA) for three markers of EED: alpha-1-antitrypsin, myeloperoxidase and neopterin. EED risk factors identified included older age, geophagy and recent acute illness. Secondly, in a birth cohort of 99 participants aged zero to nine months, 839 dual sugar absorption tests and 934 breath hydrogen tests were carried out at monthly intervals to measure EED and small intestinal bacterial overgrowth (SIBO) respectively. Stool samples were collected bi-weekly and 434 underwent ELISA for alpha-1-antitrypsin, myeloperoxidase and neopterin. Acute illness and antibiotic episodes were captured by active and passive surveillance. Breastfeeding status was recorded weekly. EED increased with age and was associated with stunting. In a multivariable model, EED was not associated with SIBO, acute illnesses, household water/sanitation/hygiene or antibiotics. In the same model, adjusted for age, EED was worse amongst those who had ceased exclusive breastfeeding, and for one EED biomarker this association was only seen during the rainy season.